Perspective of digitization from the point of view of copyright - Ramírez Marín, Carlos Adrián (2008)
Digitalization is, nowadays, a very important mechanism to help information get where it’s needed, thanks specially to the universality of internet access. However, it carries within the responsibility of making a good use of it, in means of copyright, guarding the existing legislation in Costa Rica and the international agreements in which the country takes part. Legislation allows, under certain premises, the use of digitalization. Nevertheless, it’s necessary to define the parameters in which these premises will be applied, so it’s used correctly.